2019
DOI: 10.1590/0034-7167-2017-0854
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacity and social support to people affected by cerebrovascular accident

Abstract: Objective: To investigate the functional capacity and its relationship with the level of social support to people affected by cerebrovascular accident. Methods: Cross-sectional and quantitative research, conducted with 108 individuals with sequelae of cerebrovascular accident in João Pessoa/PB. Data were collected through interviews, using a sociodemographic instrument – the Barthel Index and the Social Support Scale. Results: We observed the prevalence of functional dependency in 93.5%, and the mild depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 21 publications
1
12
0
16
Order By: Relevance
“…The functional disability after stroke occurs due to sequelae, which can be sensory, motor and/or cognitive (10) . These damages interfere with self-care, social interaction, the development of the family role, and labor (7) , resulting in losses in the execution of previously performed activities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional disability after stroke occurs due to sequelae, which can be sensory, motor and/or cognitive (10) . These damages interfere with self-care, social interaction, the development of the family role, and labor (7) , resulting in losses in the execution of previously performed activities.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified that people who did not return to labor were more prone to mood disorders and to experience limitations in family and community interaction, as well as financial problems and dissatisfaction with life, with a consequent decline in HRQoL (17,22) . besides welcoming the singularity that involves the experience of stroke survivors, considering cultures and beliefs, building a comprehensive and individual care plan that benefits the HRQoL of this population segment (10,16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This person presents specific and different care needs, such as physical help (moving to the bathroom, to the bed); communication (verbal and nonverbal cues to other family members when the patient has aphasia); support for eating, taking care of their personal hygiene and emotional support (dealing with the destructive behavior caused by the consequences of the disease) (4) . The many tasks that are attributed to the family caregiver, lack of support, unpreparedness to care, the level of dependence of the patient, the chronicity of the disabling situation, the complexity of the care activities, the worsening of health status and the uncertainty of future causes burden, and this may lead to social isolation, reduction or end of leisure activities, impairment of professional activity, loss of job and lack of time for self-care (5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…According to Chaleoykitti et al, (2020), low functional status greatly affected the quality of life of stroke patients. Social support is important for rehabilitation and reintegration into the community (Lima et al, 2019). In addition, stroke patients also need intensive health care to improve their quality of life (Pandit, 2020).…”
Section: Introductionmentioning
confidence: 99%